2019
DOI: 10.1137/18m1174428
|View full text |Cite
|
Sign up to set email alerts
|

Submodular Maximization with Uncertain Knapsack Capacity

Abstract: We consider the maximization problem of monotone submodular functions under an uncertain knapsack constraint. Specifically, the problem is discussed in the situation that the knapsack capacity is not given explicitly and can be accessed only through an oracle that answers whether or not the current solution is feasible when an item is added to the solution. Assuming that cancellation of the last item is allowed when it overflows the knapsack capacity, we discuss the robustness ratios of adaptive policies for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Disser et al [4] allowed to discard items that do not fit and showed tight competitive ratios for this case. Kawase et al [15] studied a generalization of this model in which the objective is submodular and devised a randomised competitive algorithm for this case. Since these models allow to discard items, these competitive rations do not translate to our model.…”
Section: Introductionmentioning
confidence: 99%
“…Disser et al [4] allowed to discard items that do not fit and showed tight competitive ratios for this case. Kawase et al [15] studied a generalization of this model in which the objective is submodular and devised a randomised competitive algorithm for this case. Since these models allow to discard items, these competitive rations do not translate to our model.…”
Section: Introductionmentioning
confidence: 99%